Jews of Ethiopia : the birth of an elite - Trevisan Semi, Emanuela; Parfitt, Tudor (RoutledgeCurzon Jewish studies series., 2005)
With a special focus on Europe and the role of German, English and Italian Jewish communities in creating a new Jewish Ethiopian identity, the book investigates the formation of a new Ethiopian Jewish elite.